Adjuvant radiation therapy alone is associated with improved overall survival compared to hormonal therapy alone in older women with estrogen receptor positive early stage breast cancer. (17th September 2020) - Jhawar, Sachin R.; Alpert, Naomi; Taioli, Emanuela; Sayan, Mutlay; Bazan, Jose; Park, Ko Un; Stover, Daniel; Cherian, Mathew; White, Julia; Haffty, Bruce; Ohri, Nisha
Abstract: Background: Breast conserving surgery (BCS) and adjuvant hormonal therapy (HT) without radiation therapy (RT) is an acceptable approach for older women with early stage, estrogen receptor (ER) positive breast cancer. Toxicity and compliance remain issues with HT. Adjuvant RT alone may have better compliance, but its efficacy in the absence of HT is unclear. We aim to assess patterns of adjuvant therapy and survival outcomes among older women with early stage, ER positive (ER+) breast cancer. Methods: The National Cancer Data Base (NCDB) was used to identify 130, 194 women age ≥65 years with invasive ER+, node negative breast cancer diagnosed between 2004 and 2015. All patients underwent BCS. Kaplan‐Meier survival curves were used to examine overall survival (OS). The association between adjuvant therapy and OS was assessed in multivariable Cox proportional hazards regression models. Results: Unadjusted 5/10‐year OS rates were 90.0%/64.3% for HT and RT, 84.2%/54.9% for RT alone, 78.7%/44.5% for HT alone, and 71.6%/38.0% for no treatment; p<0.001 for all. Compared to HT alone, the 10‐year multivariable hazard ratio (HR) for death for RT alone was 0.86 (95% CI 0.82‐0.91). In propensity‐matched patients who received RT alone or HT alone (n=21, 326), RT alone had significantly better survival at 5 (HRadj : 0.84) and 10 (HRadj : 0.87) years. Conclusions: Older women with early stage ER+ breast cancer who undergo BCS and receive both HT and RT have the best survival, while RT as single‐modality therapy had higher rates of OS at 5 and 10 years compared to HT alone. Abstract : In this cohort study of 130, 194 women age ≥65 years with invasive ER+, node negative breast cancer who underwent breast conserving surgery, radiation (RT) with hormonal therapy (HT) was associated with the highest 5 and 10‐year survival rates (90.0% and 64.3%, respectively). Compared to patients receiving HT alone, those receiving RT alone had improved unadjusted and adjusted survival rates.